Enhancement of the magnetoresistance at the Curie temperature of the ferromagnetic insulator La1.5Sr0.5MnRhO6 - Coldea, A; Marshall, I; Blundell, S; Singleton, J; Noailles, L; Battle, P; Rosseinsky, M (2000)
We report a study of the magnetic and electrical properties of the ferromagnetic insulator La1.5Sr0.5MnRhO6. A significant magnetoresistance is found in this system which is largest at the Curie temperature (Tc) even though there is no metal-insulator transition. The electrical transport is found to be activated above Tc and described by a variable range hopping law below Tc. Above Tc the carriers are magnetic polarons with a size which increases as the temperature approaches the magnetic transition. Rh substitution preserves ferromagnetic ordering, in contrast with the effect of other dopants on the B sites, but modifies the electrostatic potential leading to carrier localization. We attribute the peak in the magnetoresistance at Tc to the field-induced suppression of critical spin fluctuations which modulate the energetic barriers seen by the carriers.